Effect of virtual reality combined with repetitive transcranial magnetic stimulation on musculoskeletal pain and motor development in children with spastic cerebral palsy: a protocol for a randomized controlled clinical trial - Xin Li; Zefan Huang; Tijiang Lu; Juping Liang; Haibin Guo; Lixia Wang; Zhengquan Chen; Xuan Zhou; Qing Du (BMC Neurology, 2023)
Abstract Purpose This trial aims to investigate the efficacy and safety of virtual reality (VR) combined with repetitive transcranial magnetic stimulation (rTMS) for improving musculoskeletal pain and motor development in children with unilateral spastic cerebral palsy (CP). Methods This study protocol is for a randomized controlled trial consisting of 2 treatment sessions (3 days/week for 4 weeks in each session, with a 1-week interval between sessions). We will recruit children aged 3–10 years with unilateral spastic CP (Gross Motor Function Classification System level I or II). Participants will be randomly divided into 3 groups: the VR + rTMS group (immersive VR intervention, rTMS and routine rehabilitation therapy), rTMS group (rTMS and routine rehabilitation therapy), and control group (sham rTMS and routine rehabilitation therapy). VR therapy will involve a daily 40-minute movement training session in a fully immersive environment. rTMS will be applied at 1 Hz over the primary motor cortex for 20 min on the contralateral side. The stimulation intensity will be set at 90% of the resting motor threshold, with 1200 pulses applied. A daily 60-minute routine rehabilitation therapy session including motor training and training in activities of daily living will be administered to all participants. The primary outcome will be pain intensity, assessed by the Revised Face, Legs, Activity, Cry, and Consolability Scale (R-FLACC). The secondary outcomes will include motor development, evaluated by the 66-item version of the Gross Motor Function Measure (GMFM-66) and Fine Motor Function Measure (FMFM); balance capacity, measured by the interactive balance system; activities of daily living; and quality of life, measured by the Barthel index and the Chinese version of the Cerebral Palsy Quality of Life scale for Children (C-CP QOL-Child). Safety will be monitored, and adverse events will be recorded during and after treatment. Discussion Combined application of VR therapy and rTMS may reveal additive effects on pain management and motor development in children with spastic CP, but further high-quality research is needed. The results of this trial may indicate whether VR therapy combined with rTMS achieves a better analgesic effect and improves the motor development of children with spastic CP. Trial registration Registration number: ChiCTR230069853. Trial registration date: 28 March 2023. Prospectively registered.